Effects of seasonality on drosophilids (Insecta, Diptera) in the northern part of the Atlantic Forest, Brazil. Issue 5 (2nd March 2017) - Coutinho-Silva, R.D.; Montes, M.A.; Oliveira, G.F.; de Carvalho-Neto, F.G.; Rohde, C.; Garcia, A.C.L.
Abstract: Seasonality is an important aspect associated with population dynamic and structure of tropical insect assemblages. This study evaluated the effects of seasonality on abundance, richness, diversity and composition of an insect group, drosophilids, including species native to the Neotropical region and exotic ones. Three preserved fragments of the northern Atlantic Forest were surveyed, where temperatures are above 20 °C throughout the year and rainfall regimes define two seasons (dry and rainy). As opposed to other studies about arthropods in tropical regions, we observed that abundance of drosophilids was significantly higher in the dry season, possibly due to biological aspects and the colonization strategy adopted by the exotic species in these environments. Contrarily to abundance, we did not observe a seasonal pattern for richness. As for other parts of the Atlantic Forest, the most representative Neotropical species ( Drosophila willistoni, D. sturtevanti, D. paulistorum and D. prosaltans ) were significantly more abundant in the rainy season. Among the most abundant exotic species, D. malerkotliana, Zaprionus indianus and Scaptodrosophila latifasciaeformis were more importantly represented the dry season, while D. simulans was more abundant in the rainy period. The seasonality patterns exhibited by the most abundant species were compared to findings published in other studies. Our results indicate that exotic species were significantly more abundant in the dry season, while native ones exhibited an opposite pattern.